Abordajes sobre el Pasado Reciente en Uruguay: La trayectoria del Equipo de Investigación Histórica en la Universidad de la República. 2005-2015 - Fabiana Larrobla Caraballo; Magdalena Figueredo Corradi (Les Cahiers ALHIM)
Since the end of the dictatorship and until the end of the XX century, issues related to human rights violations and crimes against Humanity had been excluded from the public agenda. Only in the year 2000, and with President Batlle’s administration some of the perspectives regarding the Recent Past gained relevance and were integrated into the political agenda. But it will be with the assumption of the first leftist government in 2005 that a more significant change will occur. In this context the new administration summons the University of the Republic to address the investigation of what happened with the detained-disappeared and the search for their remains. Within this framework, the Historical Research Team emerges, the central axis of this article. In this way, we will explore its course of work, the methodological options, the transformations and the extension of its tasks and research objectives and the impact generated from the support for Justice in criminal complaints for crimes against humanity.